2011
DOI: 10.1016/j.jbiomech.2011.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Computational wear simulation of patellofemoral articular cartilage during in vitro testing

Abstract: Though changes in normal joint motions and loads (e.g., following anterior cruciate ligament injury) contribute to the development of knee osteoarthritis, the precise mechanism by which these changes induce osteoarthritis remains unknown. As a first step toward identifying this mechanism, this study evaluates computational wear simulations of a patellofemoral joint specimen wear tested on a knee simulator machine. A multi-body dynamic model of the specimen mounted in the simulator machine was constructed in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Computer simulations can apply large loads and duplicate weight-bearing activities using musculoskeletal models that can diminish the limitations of clinical and cadaveric experimental studies. Several previous papers used simulations to predict postoperative flexion angle, knee kinematics, joint load, and damage to the insert [18][19][20][21]. These results were validated by clinical data [20] and implant retrieval findings [21].…”
mentioning
confidence: 80%
“…Computer simulations can apply large loads and duplicate weight-bearing activities using musculoskeletal models that can diminish the limitations of clinical and cadaveric experimental studies. Several previous papers used simulations to predict postoperative flexion angle, knee kinematics, joint load, and damage to the insert [18][19][20][21]. These results were validated by clinical data [20] and implant retrieval findings [21].…”
mentioning
confidence: 80%
“…We are pursuing these with collaborations at Brown University and University of Auckland, including the potential use of high-resolution registration with dual fluoroscopy [73,104]. The computational methods employ either statistical shape modeling [5,41,66] or rigid body dynamics [41], integrating 3-D data to develop subject-specific models to predict changes over time, such as patterns of joint degeneration, response to fracture, or ligament disruption.…”
Section: Next Stepsmentioning
confidence: 99%
“…This suggests that initial configuration of registration volumes may be important and should be carefully considered for acquiring contact data using image registration. Li et al (2011) demonstrated changes in femoral and patellar wear contact areas of up to 5% with variations in pose. Fregly et al (2008) showed variations in contact parameters after knee replacement of up to 1157% with errors in translation and rotation.…”
Section: Discussionmentioning
confidence: 99%
“…However, when using registration to acquire transformations from image sets such as MRI, the initial configuration of the registration volumes may potentially influence the final outcome. Contact mechanics simulations may be subsequently affected and studies have shown contact parameters to be sensitive to variations in initial alignment (Li et al 2011). It is possible that the results of automatic registration are sensitive to initial alignment of the images, and that the further apart the registration volumes, the less likely that automatic registration provides a good solution.…”
Section: Introductionmentioning
confidence: 99%